Strategi Dakwah Muhammadiyah di Era Digitalisasi : Inovasi dan Tantangan - Riyan Muhammad; Milana Abdillah Subarkah (Student Research Journal, 2024)
Nowadays, the development of the digital world has had a significant impact on the practice of da'wah, making social media a vital means of conveying religious teachings or messages. In this context, Muhammadiyah, as one of the largest Islamic organizations in Indonesia, faces new challenges and opportunities in preaching. With digital technology, da'wah messages are now more easily accessible and disseminated, allowing for a wider and more flexible reach. However, there is a digital inequality that affects the effectiveness of da'wah, where some community groups may be left behind in accessing information. This research aims to explore Muhammadiyah's da'wah strategy in the era of digitalization, identifying the innovations implemented and the challenges faced. Through this research, the author aspires to be able to provide scientific treasures, generally for preachers or religious figures in optimizing an inclusive and relevant da'wah approach in the midst of rapid technological change.